Sex-specific modulation of juvenile social play behavior by vasopressin and oxytocin depends on social context - Bredewold, Remco; Smith, Caroline J. W.; Dumais, Kelly M.; Veenema, Alexa H. (Frontiers in Behavioral Neuroscience, 2014)
We recently demonstrated that vasopressin (AVP) in the lateral septum modulates social play behavior differently in male and female juvenile rats. However, the extent to which different social contexts (i.e., exposure to an unfamiliar play partner in different environments) affect the regulation of social play remains largely unknown. Given that AVP and the closely related neuropeptide oxytocin (OXT) modulate social behavior as well as anxiety-like behavior, we hypothesized that these neuropeptides may regulate social play behavior differently in novel (novel cage) as opposed to familiar (home cage) social environments. Administration of the specific AVP V1a receptor (V1aR) antagonist (CH2)5Tyr(Me2)AVP into the lateral septum enhanced home cage social play behavior in males but reduced it in females, confirming our previous findings. These effects were context-specific because V1aR blockade did not alter novel cage social play behavior in either sex. Furthermore, social play in females was reduced by AVP in the novel cage and by OXT in the home cage. Additionally, females administered the specific OXT receptor antagonist desGly-NH2,d(CH2)5-[Tyr(Me)2,Thr4]OVT showed less social play in the novel as compared to the home cage. AVP enhanced anxiety-related behavior in males (tested on the elevated plus-maze), but failed to do so in females, suggesting that exogenous AVP alters social play and anxiety-related behavior via distinct and sex-specific mechanisms. Moreover, none of the other drug treatments that altered social play had an effect on anxiety, suggesting that these drug-induced behavioral alterations are relatively specific to social behavior. Overall, we showed that AVP and OXT systems in the lateral septum modulate social play in juvenile rats in neuropeptide-, sex- and social context-specific ways. These findings underscore the importance of considering not only sex, but also social context, in how AVP and OXT modulate social behavior.